Review: Persistent spontaneous synovial drainage from digital flexor sheath in proliferative tenosynovitis: Two case reports and a review of the literature. Issue 2 (May 2015) - Chin, Brian; Cheung, Kevin; Farhangkhoee, Hana; Thoma, Achilleas
Proliferative flexor tenosynovitis of the hand is an inflammatory process involving the synovial sheaths surrounding the tendons. It is most commonly caused by infection, but may also be caused by overuse, diabetes and rheumatic conditions such as rheumatoid arthritis and crystal arthropathies. The present report describes two patients with severe proliferative tenosynovitis, who developed a fistula between the tendon sheath and skin after instrumentation, resulting in persistent synovial drainage. After failing conservative management, both patients were managed with extensive flexor tenosynovectomy to prevent inoculation of bacteria into the flexor sheath. The presentation, management and outcome of each case is described in addition to a discussion of the literature on tenosynovial fistulas.